Morphological and Chemical Characterization of Titanium and Zirconia Dental Implants with Different Macro- and Micro-Structure - Maria Menini; Francesco Pera; Francesco Bagnasco; Francesca Delucchi; Elisa Morganti; Luigi Canullo; Paolo Pesce (Applied Sciences, 2020)
Background: The aim of this study was to evaluate the macro- and micro-structure and the chemical composition of the surface of 5 different commercially available dental implants. Roughness values were also calculated. Materials and Methods: 1 zirconia implant (NobelPearl of Nobel Biocare) and 4 titanium implants, Syra (Sweden&Martina), Prama (Sweden&Martina), T3 (Biomet 3i), and Shard (Mech&Human), were analyzed through SEM-EDX analysis and quantitative evaluation of surface roughness (1 sample), and XPS chemical analysis (1 sample). Surface roughness was quantitatively assessed using the stereo-SEM method (SSEM). The following area roughness parameters were calculated, according to ISO25178: Sa, Sz, and Sdr. Results: From the SEM observations, all the implants analyzed presented modern well-developed micro-structures as the result of the specific process of double acid etching alone or combined with other additional treatments. Roughness values were generally greater at the level of the implant body and lower at the collar. The chemical characterization of the implant surfaces exhibited excellent results for all of the implants and indicated good care in the production processes. Conclusions: All the samples were well-conceived in terms of topography and surface roughness, and clean in terms of chemical residues.